Enhancing Teaching Productivity Among University Staffers: The Influence of Organizational Commitment and Workload - Fehintola Victor A; Teresa Ngozi Onyemah; Ishola Samiat A; Naseem Akorede Raji; A. O Sylvester; Habeeb Omoponle Adewuyi (MASI Mandiri Edukasi, 2024)
The declining level and quality of productivity in the educational sector have become a cause for concern among stakeholders. This study investigated the connection between workers' organisational commitment, workload, and productivity among university staff in Oyo and Osun states. The descriptive research design was utilised, and data were collected from two public universities in each state. Valid and standardised instruments were used, including the Quantitative Workload Inventory, Work Productivity Survey, and Organizational Commitment Scale. Pearson correlation and regression analyses were conducted. The results revealed significant correlations between productivity and workload (r = .039, p < .05) and organisational commitment (r = .044, p < .05). Workload contributed the most (Beta = .425, t = 6.015, p < .05) productivity prediction, followed by organisational commitment (Beta = .284, t = 5.116, p < .05). These findings highlight the need for the educational sector to address the dangers posed by excessive workload and lack of organisational commitment. It is recommended that measures be implemented to manage these factors effectively, including improving working conditions, enhancing welfare packages, and ensuring prompt payment of salaries and allowances for university staff.